The oasis tourism product between the richness of diversity and the dangers of climate change: The oases of Tighmert and Asrir as a case study (Province of Guelmim, Morocco) - ELBAIED, Said; COUISSI, Tarik; KASBAOUI, Abderrahim (Journal of natural sciences, life and applied sciences, 2021)
The climate change that the world is currently witnessing is considered as one of the most important concerns of countries, whether they are advanced or backward. Morocco, in turn, has not been spared from these changes because of its geographical location, and although the environmental problems facing Morocco today are not new, the understanding of its dimensions has come somewhat late, after noticing the impact of environmental degradation affecting the oases of southern Morocco. Thus, the oases of Tighmert and Asrir have not been spared from this deterioration, which has contributed to the weakening of economic development and diminished its potential.Nowadays, there are few exploratory studies that have been conducted on the relationship between the tourism and the probable impacts of climate change. The need to address several basic points, including deep knowledge of tourism requirements and needs for adaptation to climate, the environment, weather conditions, early monitoring, the sensitivity of various products and tourism services, and their impact on climate change, to develop scenarios for the potential risks and threats related to climate change in the two oases. Therefore, serious efforts should be made to identify other sustainable means of tourism that may be less sensitive to climate change and its effects, and the integrated and comprehensive planning are needed to enhance the success of the future path of oasis tourism development.The aim of this study is to highlight the climate risks that threaten the two oases in the Guelmim province. The climate has implications for many environmental resources that are important foundations for tourism development, and some of them are severely affected, in different ways, by climate variability and change. Thence, the efforts that made by the preparers of space to cope with the effects of climate change, whether by respecting and applying international measures to reduce global warming, or through a national policy aimed at preserving the environment and achieving sustainable tourism development in the oasis systems, or through a local policy that is supervised by those involved in this promising area. This study also aims to show the extent to which tourism can be adopted as an alternative and a development supplement that seeks to promote the oasis economy within the framework of managing scarcity.
Keywords: climate change; sustainable tourism; oasis ecosystems; oasis economy; adaptation; mitigation; early monitoring; risk management; scarcity management; alternative tourism